Technological aspect factors of E-learning readiness in higher education institutions: Delphi technique - Al-araibi, Asma Ali Mosa; Mahrin, Mohd Naz’ri bin; Yusoff, Rasimah Che Mohd (Education and information technologies, 2019)
E-learning is an educational method which aims to provide educational or training programs for students or trainees at any time and at any place using information and communication technology (ICT). Increasing numbers of higher education institutions have adopted e-learning in order to take advantage of the opportunities that it offers. Through e-learning, learners can access resources and information from anywhere and at any time. However, the successful implementation of e-learning relies on the readiness to be able to initiate this system because, without proper readiness, the project will probably fail. E-learning readiness refers to the assessment of how ready an institution is to adopt and implement e-learning. E-learning readiness helps higher education institutions to measure their stages of readiness, identify any gaps, and then redesign its strategy in order to adopt the e-learning system. One of the most important aspects of e-learning readiness is the technological aspect, which plays an important role in implementing an effective and efficient e-learning system. There is a lack of agreement about the factors that shape the technological aspects of e-learning readiness; hence, a clear gap has been identified in the knowledge on the technological aspects of e-learning readiness. The aim of this paper is to review the technological factors of e-learning readiness by performing the Delphi technique, and develop an initial model for technological aspects of e-learning readiness in higher education institutions. It is anticipated that this model can help institutions of higher education to identify and understand the technological aspects that must be considered when assessing the readiness to apply an e-learning project.